Pengaruh Sales Promotion dan Personal Selling Terhadap Keputusan Pembelian Sepeda Motor Yamaha Di Kota Jombang (Studi Kasus di Dealer Sentra Sentosa Motor) - Mochamad Wahyu Satrio Putro; Rohmad Prio Santoso (BIMA : Journal of Business and Innovation Management, 2020)
The purpose of this research is to analyze the impact of sales promotion and personal selling on Yamaha motor purchase decision in Jombang (study case at Sentra Sentosa Motor Dealer). The research using 70 random samples of customers that have make decision to buy Yamaha motorcycle by distribute questionnaire to them. The methodology of this research is quantitative with causal analysis methode. The data analysis technique using double linear regression. The result of this research showed that: (1) partially, sales promotion has significant effect on Yamaha motor purchase decision at Sentra Sentosa Motor dealer Jombang. (2) partially, personal selling has significant effect on Yamaha motor purchase decision at Sentra Sentosa Motor dealer Jombang. (3) simultaniously, sales promotion and peesonal selling have impact on Yamaha motor purchase decision at Sentra Sentosa Motor dealer Jombang.